Memória e outros endofenótipos cognitivos no diagnóstico da esquizofrenia - João Marques Teixeira (2005)
The author proposes that the evaluation of the schizophrenic cognitive deficit sub-types would be included in the mental disorders diagnostic systems, complementing clinical and syndromatic criteria, based on the evidence and on the most recent consensus regarding schizophrenia cognitive deficits characteristics. In this way, the author suggests that the diagnosis would reflect the underlying altered neurobiologic processes.